Protecting the Right to Know in Japan: Social Advocacy versus the Special Secrecy Law. - Kuzina, Viktoriya (fi=Turun yliopisto|en=University of Turku|, 2017)
Present research deals with the civil society and social advocacy regarding the Special Secrecy Law in contemporary Japan. The purpose of this work is to examine the ability of the civil society groups to influence the governmental policymaking by tracking the activities of an NGO network in its resistance towards the Special Secrecy Law in a case study, which acts as a mean to examine the process of influencing governmental decision making. The ability to make such an impact is measured through a scale of strictly defined factors, such as ability to draw attention of the mass media to the problem, ability to influence the opinion polls, etc. This thesis utilizes discourse analysis, quantitative and qualitative archival materials of the chosen NGO network and five major Japanese newspapers to examine the process and means of influencing the policymaking by studying the NGO network’s activities and their outcomes, and measuring those to the set of measuring factors. I found out that despite the vast grassroots support and increasing professional input within the civil society, social advocacy in Japan has no influence on the governmental policymaking. Nevertheless, it has the ways to communicate the information down towards the citizens as well as communicate its concerns up to the state very clearly by maintaining a lot of channels. The NGO network does not have much back-up from non-Japanese actors, but it has a solid national support within the country. When the attempt of the NGO network to stop the promulgation of the ambiguous and potentially dangerous law failed, the examined NGO network turned to the educational activities aiming spread of information about the law and methods of protection for Japanese NGOs operating outside Japan or working with other entities and individuals outside Japan, which might be influenced by the Special Secrecy Law. Thus, with no power to influence the policymaking, civil society in Japan has a lot of resources to create awareness and provide assistance in order to limit the impact of the law. Present research may become of use to those who are interested in the changing dynamics of the civil society in East Asian countries and in Japan in particular. The law might also be studied in the context of influencing the foreign policies of Japan, media-scape within the country or probability of changing the Constitution of Japan through adoption of the laws of a similar nature, as for example, the newly suggested Conspiracy law.